Histórico de periodontite crônica e aumento da relação RANKL/OPG estão associados com a doença peri-implantar - Costa, Lucas Carneiro (2014)
History of chronic periodontitis (CP) is a risk factor for osseointegration failure. The osteoclastogenesis system, which includes the receptor activator of nuclear factor-kappa B (RANK), RANK ligand (RANKL) and osteoprotegerin (OPG), is critical for homeostatic control of osteoclast activity, suggesting the system s vital role in the progress of bone loss. In this study, we investigated the levels of OPG and RANKL in healing peri-implant tissues from subjects volunteer with and without a history of CP and their association with uneventful osseointegration. Diagnosis of a history of CP and peri-implant examination was performed on 49 subjects volunteer. Based on periodontal status, subjects were divided into a control group (without history of CP, n= 26) and a CP group (with history of CP, n= 23). Gingival biopsies were harvested from all subjects during implant exposure. Livak Method determined the relative quantification of OPG/RANKL expressions in a quantitative polymerase chain reaction system. OPG and RANKL proteins were analyzed using western blot and immunohistochemistry assay. Non-parametric Mann-Whitney test correlated the levels of OPG and RANKL in each group (p<0.05). Twenty-four (92.3%) subjects in the control group showed uneventful peri-implant healing during osseointegration, in contrast with 7 (30,4%) in the CP group. Subjects with CP history had 27 times higher chance of developing harmful peri-implant healing, including mucosae inflammation and/or implant loss compared to subjects without CP history (p=0.0001; 27.43 [4.28-228.63]). OPG showed similar mRNA levels in both groups (p=0.22). However, high levels of RANKL were observed (p=0.04) in the CP group. In addition, RANKL/OPG mRNA expressions showed higher association with history of chronic periodontitis (p=0.001). The western blot and immunohistochemistry analyses showed the increase of RANKL levels in opposition to decrease OPG expression in CP patients. In conclusion, even without active periodontitis, subjects with a history of CP had elevated tissue levels of RANKL/OPG and higher correlation with peri-implant mucosae inflammation and implant loss.